2016
DOI: 10.1161/circresaha.116.308559
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelium-Derived 5-Methoxytryptophan Is a Circulating Anti-Inflammatory Molecule That Blocks Systemic Inflammation

Abstract: Rationale: Systemic inflammation has emerged as a key pathophysiological process that induces multiorgan injury and causes serious human diseases. Endothelium is critical in maintaining cellular and inflammatory homeostasis, controlling systemic inflammation, and progression of inflammatory diseases. We postulated that endothelium produces and releases endogenous soluble factors to modulate inflammatory responses and protect against systemic inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 46 publications
2
111
0
Order By: Relevance
“…In terms of future directions, this report 20 opens the door for investigations of the specific stimuli leading to production of 5-MTP, the cellular mechanisms of action of 5-MTP, and the pathways through which it is exported. Because the authors determined the location of 5-MTP in the cytoplasm and because eNOS translocation from the cell membrane to the cytosol is a requirement for the development of hyperpermeability 2124 , it is tempting to speculate that 5-MTP may reduce transport of macromolecules across microvascular walls by returning eNOS from the cytoplasm to the cell membrane or by inhibiting the synthesis of eNOS-derived NO in the cytoplasm.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of future directions, this report 20 opens the door for investigations of the specific stimuli leading to production of 5-MTP, the cellular mechanisms of action of 5-MTP, and the pathways through which it is exported. Because the authors determined the location of 5-MTP in the cytoplasm and because eNOS translocation from the cell membrane to the cytosol is a requirement for the development of hyperpermeability 2124 , it is tempting to speculate that 5-MTP may reduce transport of macromolecules across microvascular walls by returning eNOS from the cytoplasm to the cell membrane or by inhibiting the synthesis of eNOS-derived NO in the cytoplasm.…”
mentioning
confidence: 99%
“…Wang et al 20 add a new molecule of endothelial origin as an anti-inflammatory agent in their article "Endothelium-derived 5-methoxytryptophan is a circulating anti-inflammatory molecule that blocks systemic inflammation" in this issue of Circulation Research . The authors extracted and identified 5-methoxytryptophan (5-MTP) from endothelial cell-conditioned medium (EC-CM).…”
mentioning
confidence: 99%
See 3 more Smart Citations